Temperature- and Pressure-Reducing Regimes in the Growth Cell of HPHT Diamonds, Optimal for Preserving Crystal Integrity after Growth Completion - Nikolay I. Alekseyev; Anton P. Broyko; Ivan K. Khmelnitskiy; Alexander V. Kolyadin; Vagarshak M. Aivazyan; Ivan V. Oreshko (C, 2023)
With its exceptional strength characteristics, diamond has some mechanical drawbacks, significant brittleness being among them. In particular, some HPHT-grown diamonds crack when the extreme parameters inherent to the diamond growth process gradually decrease. The cracking is caused by excessive stress due to the poor plastic properties of the diamond growth catalytic medium at certain stages of reducing the pressure and the temperature. An insulating container with the growth cell and heating circuit fragment inside can also make a significant contribution to the probability of cracking. This paper considers the possibility of minimizing the mechanical stress in the growth cell and, consequently, in the diamond crystal by choosing the optimal trajectory for the decrease in the pressure and temperature from diamond growth conditions to normal conditions.